Islamic Religious Education (PAI) Learning Based on The Independent Curriculum of Elementary School at Yogyakarta - Ahmad Salim (Ta'dib, 2023)
The purpose of this study was to reveal the implementation of Independent Curriculum-based PAI learning and the obstacles encountered in its implementation in SDN Semarangan 4, SDN Semarangan 5, SDN Pengkol, SDIT Ibnu Abbas, SDN 2 Godean, SDN Timon. The method used in this study is qualitative descriptive with a phenomenological design. Data collection was carried out through in-depth interviews with 6 PAI teachers as key informants, as well as observations. The results of the study show that the implementation of learning begins with greetings, apperceptions, basic activities with various methods and approaches used. Assessment is done in different ways, not only relying on exams, but reflection on learning activities is an important aspect of the assessment instrument. Freedom in achieving PAI learning is an important point in this independent curriculum, teachers and students have the freedom to master certain material until it is completed in one semester. Developing an attitude of independence is part of Pancasila's student profile building project. Obstacles encountered in the implementation of the Independent Curriculum, namely the teacher's difficulties in translating the curriculum to strengthen the profile of the Pancasila student into project activities outside of learning